ON BOUNDEDNESS AND COMPLETE POSITIVITY OF MAPS ON BANACH ALGEBRAS - Okelo, N. B. (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
Let and Â be algebras, andÂ Â be by Â matrices with entries from and Â respectively and Â be a linear map, then we define maps Â Â Â by Â for all natural numbers . We determine conditions under whichÂ Â is positive for all Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords: Hermitian maps, unital -homomorphism and completely positive maps.